Damming the narmada - "Alvares, Claude" (Dehradun, 1988)
In the past few years, there has been a growing chorus of scientific opinion that big dams cause much more harm than good. These dams not only dislocate the homes and livelihood of mainly rural and tribal peoples but also devastate the environment, drown the forests with their fauna and flora, and give rise to other hand ecological and health consequencies.
Keywords: Narmada dams